Copper-based graphene high-thermal-conductivity composite alloy material and preparation method thereof
By using additive manufacturing technology and alternating deposition method to construct a directed channel structure in copper-based graphene composite materials, the problem of insufficient continuity and orientation consistency of graphene layer sheets is solved, and copper-based graphene with high thermal conductivity is achieved The preparation of composite alloy materials has improved the heat dissipation efficiency of the motor control system of new energy vehicles.
Patent Information
- Application Number
- CN202411588092.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
Among the existing copper-graphene composite materials, the continuity and orientation consistency of graphene layer sheets are poor, which limits the improvement of its thermal conductivity and is difficult to meet the needs of efficient heat dissipation in the motor control system of new energy vehicles.
The channel structure with directional arrays is constructed through additive manufacturing technology, and a small layer of graphene and copper-graphene mixture is deposited alternately on the pore surface by chemical vapor deposition and electrodeposition method, combining pure copper liquid or copper-graphene. The mixture fills the pores to form a copper-based graphene composite alloy material with high thermal conductivity.
The continuous distribution and high orientation consistency of the graphene layer in the three-dimensional structure are achieved, and the thermal conductivity of the material is improved, reaching more than 500 Wm-1K-1, surpassing the thermal conductivity of traditional block materials.
Smart Images

Figure CN119457121A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of heat conduction of copper-based alloy materials, and in particular relates to a method for preparing a copper-based graphene heat-conducting alloy material. Background Art
[0002] With the rapid and in-depth implementation of the "dual carbon" policy, the elimination of old fuel vehicles has accelerated, and the sales restrictions on new fuel vehicles have continued to increase. my country's new energy vehicle industry is showing an accelerated development trend. The "New Energy Vehicle Industry Development Plan (2021-2035)" proposes that by 2025, the sales volume of new energy vehicles will account for about 20% of the total sales volume of new vehicles. By 2035, new energy vehicles will become mainstream models, and public vehicles will be fully electrified. In 2023, China's new energy vehicle production and sales will reach 9.587 million and 9.495 million respectively, up 35.8% and 37.9% year-on-year, respectively, with a market share of 31.6%.
[0003] The heat dissipation performance of the power module and electronic components of the motor control system in new energy vehicles directly affects the stability, efficiency and life of the entire system. Therefore, how to effectively control the system temperature and avoid overheating of components has become an important challenge in technology research and development. At present, commonly used high thermal conductivity materials include thermal conductive silicone, thermal conductive gaskets, thermal conductive graphite sheets, copper-based and aluminum-based metal materials, ceramic materials and composite materials. These materials can effectively improve the heat dissipation efficiency and reduce the operating temperature of the system by optimizing thermal conductivity, high temperature resistance and electrical insulation. With the development of miniaturization and high power trends in motor control systems, traditional thermal conductive materials have been difficult to meet the needs of efficient heat dissipation. Therefore, materials with high thermal conductivity and meeting system structure requirements have become a key research and development direction.
[0004] Composite materials of copper and graphene have great potential in the development of high thermal conductivity materials, but the lateral size, distribution uniformity, and orientation consistency of graphene flakes in the copper matrix are the main limiting factors in the development of such materials.
[0005] Patent CN107460483A uses a method of electroplating copper on the surface of a graphite film, then baking and rolling. Patent CN117702115A uses a slurry coating method to coat graphene oxide on a porous copper foil surface to produce a copper-graphene composite film with high thermal conductivity. Patent CN118360514A mixes high-purity copper powder and graphene powder and sintering them to obtain a copper-graphene composite material with good uniformity, with a thermal conductivity of 408.9 Wm -1 K -1 above.
[0006] From the above patents, it can be seen that high thermal conductivity copper-graphene composite materials include two types: two-dimensional thin films and three-dimensional bulk materials. The continuity and orientation consistency of the graphene layer in the thin film material are good, but its size in the thickness direction limits the heat dissipation rate. The continuity and orientation consistency of the graphene flakes in the bulk material are very poor, which limits the improvement of its thermal conductivity. Therefore, improving the continuity and orientation consistency of the graphene flakes in the bulk copper-graphene composite material is a problem to be solved. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a high thermal conductivity copper-based graphene composite alloy material and a preparation method thereof, which can realize the orderly three-dimensional construction of the high thermal conductivity copper-based graphene composite alloy material to improve the heat dissipation performance of motor control system power modules and electronic components in new energy vehicles.
[0008] The present invention is achieved through the following technical solutions: A high thermal conductivity copper-based graphene composite alloy material and a preparation method thereof, wherein graphene nanosheet powder and copper powder are mixed to form a uniform mixed powder. The mixed powder is constructed into a matrix containing a pore structure arranged in a directed array by using additive manufacturing technology. A few layers of graphene are deposited on the surface of the pores by using chemical vapor deposition, or a few layers of graphene and a copper-graphene mixture are alternately deposited on the surface of the pores by using chemical vapor deposition and electrodeposition. The pore structure is filled with pure copper liquid or a copper-graphene mixture to form a copper-based graphene composite alloy material with high thermal conductivity.
[0009] Furthermore, the copper powder particles have a diameter of 1-50 μm, the graphene nanosheets have a thickness of ≤3 layers, and a diameter of less than 5 μm. The mass fraction of the graphene nanosheets in the copper-graphene mixed powder is between 0.1% and 1%.
[0010] Furthermore, the copper powder and the graphene nanosheets are mixed by ball milling, ultrasonic dispersion, deposition or wet mixing.
[0011] Furthermore, the additive manufacturing method adopts laser selective melting or electron beam selective melting method.
[0012] Furthermore, the additively manufactured porous channel structure includes a rectangular, circular, regular hexagonal, three-periodic minimum surface configuration, a channel size of less than 2 mm, a channel wall thickness of 0.5-2 mm, and the channels are radially distributed from the center of the heat source to the periphery.
[0013] Furthermore, the deposit on the surface of the pores: Since the thermal conductivity of graphite is much lower than that of graphene, the number of graphene layers needs to be controlled to ensure the high thermal conductivity of graphene. The number of graphene layers deposited by chemical vapor deposition is less than 5, and the thickness of each layer of pure copper and copper-graphene mixture is ≤10 μm. If the pore size is ≤0.5 mm, only chemical vapor deposition is used to deposit graphene on the pore surface. If the pore size is greater than 0.5 mm, chemical vapor deposition and electrodeposition are used to alternately deposit graphene and copper-graphene mixture on the pore surface until the pore size is ≤0.5 mm or the pore is filled.
[0014] Furthermore, when the pores are not completely filled, pure copper liquid or copper-graphene mixture is used to fill the pores. The temperature of the filling liquid pure copper and the liquid pure copper-graphene nanosheet mixture is less than 20° C. above the melting point of pure copper.
[0015] Furthermore, the mass fraction of graphene nanosheets in the liquid pure copper-graphene nanosheet mixture is between 0.1% and 1%.
[0016] The beneficial effects of the present invention are:
[0017] The three-dimensional porous channel structure is constructed using additive manufacturing technology, which achieves the orderly manufacturing of the porous structure and thereby improves the orientation consistency of the graphene layer in the three-dimensional structure.
[0018] The combination of additive manufacturing technology and chemical vapor deposition can achieve the continuous distribution of graphene layers in the three-dimensional pore structure.
[0019] Chemical vapor deposition and electrodeposition are used alternately to deposit graphene and copper-graphene mixtures, which can prevent the graphene layer from being too thick.
[0020] Filling the pores with pure copper liquid or a copper-graphene mixture can avoid the negative effect of the pores on thermal conductivity.
[0021] The thermal conductivity of the copper-based graphene composite alloy prepared by the method of the present invention reaches 500 Wm -1 K -1 , which is higher than the thermal conductivity of the bulk material prepared by mixed sintering of copper and graphene powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a flowchart of a method for preparing a copper-based graphene high thermal conductivity composite alloy material in the abstract of the present invention.
[0023] Figure 2 This is a diagram of the porous structure model in implementation case 1.
[0024] Figure 3 This is a diagram of the porous structure model in implementation case 2.
[0025] Figure 4 This is a diagram of the porous structure model in implementation case 3.
[0026] Figure 5 This is a diagram of the porous structure model in implementation case 4. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] On the contrary, the present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention as defined by the claims. Further, in order to make the public have a better understanding of the present invention, some specific details are described in detail in the detailed description of the present invention below. Those skilled in the art can fully understand the present invention without the description of these details.
[0029] Implementation Case 1
[0030] The graphene nanosheet powder and the copper powder were mixed together by ball milling to obtain a uniformly mixed powder. The average particle diameter of the copper powder was 32 μm, the number of layers of the graphene nanosheet was about 3, and the average in-plane size was 4.3 μm. The mass fraction of the graphene nanosheet in the mixed powder was about 0.7%.
[0031] The selective laser melting method is used to manufacture Figure 2 The cross section shown is a square channel structure, and the channel adopts a radial distribution from the central heat source to the edge. The side length of the channel cross section square is 0.5 mm, and the wall thickness is 1 mm. The channel direction is the width direction of the rectangular block structure. The size of the rectangular block structure is 4 mm × 25 mm × 50 mm.
[0032] The surface of the porous structure manufactured by laser selective melting additive manufacturing was pretreated with a solution of phosphoric acid (H3PO4): 60%, sulfuric acid (H2SO4): 30%, and water: 10% to remove residual powder and protrusions and clean the surface.
[0033] A graphene layer with a thickness of about 4 layers is deposited on the surface of the porous channel by chemical vapor deposition. In the chemical vapor deposition method, CH4 is used as the carbon source and hydrogen is used as the protective gas. The deposition temperature is 1000°C.
[0034] The microchannel structure was filled with pure copper liquid at a temperature of 1096°C. Finally, a copper-based graphene high thermal conductivity composite alloy was obtained with a thermal conductivity of up to 503.2 Wm -1 K-1 .
[0035] Implementation Case 2
[0036] The copper powder and the graphene powder were uniformly mixed in ethanol by ultrasonic dispersion to obtain a uniform mixed powder. The specifications of the copper powder and the graphene powder were the same as those in Example 1. The mass fraction of the graphene nanosheets in the mixture was 0.5%.
[0037] The mixed powder is constructed into a distribution such as Figure 3 The diagonally distributed square cross-section porous channel structure shown has a side length of 1 mm at the channel interface square, and the minimum wall thickness between adjacent channels in two perpendicular directions is 0.5 mm and 1 mm respectively. The internal structure of the channel is the same heat source center to the surrounding radiation structure as in Example 1. The channel direction is the width direction of the rectangular structure. The size of the rectangular block structure is 4 mm × 25 mm × 50 mm.
[0038] The surface pretreatment method of the additively manufactured porous channel structure is the same as that in Implementation Case 1.
[0039] Graphene layers and copper-graphene mixture layers were alternately deposited by chemical vapor deposition and electrodeposition. The chemical vapor deposition method used was the same as that in Example 1. In the electrodeposition method, the electrolyte was a solution of copper sulfate (CuSO4) and sulfuric acid (H2SO4), with the following ratio: copper sulfate (CuSO4·5H2O): 0.2 M, sulfuric acid (H2SO4): 0.1 M. The concentration of graphene in the mixed solution was 0.05 mg / mL. In order to avoid graphene agglomeration, polyvinyl pyrrolidone (PVP) was used as a dispersant, and the proportion of the dispersant to the total amount of graphene was 0.1 wt%. The deposition current was 0.5 A / dm². The thickness of the electrodeposited copper-graphene layer was 10 μm. A total of 20 alternating depositions were performed.
[0040] The porous structure filling method is the same as that of implementation case 1.
[0041] Implementation Case 3
[0042] The mixing method of copper powder and graphene powder is the same as that of Implementation Example 1, the average particle diameter of copper powder is 20 μm, and the specifications of graphene nanosheets are the same as those of Implementation Example 1. The mass fraction of graphene nanosheets in the mixed powder is about 1%.
[0043] The additive manufacturing method in Example 1 is used to construct Figure 4The cross section shown is a regular hexagonal porous channel structure with a side length of 0.8 mm. The minimum wall thickness between adjacent channels is 0.2 mm, and the interior of the channel is a parallel distribution of hexagonal channels. The cross section of the rectangular structure parallel to the channel is a square. The size of the rectangular block structure is 4 mm × 25 mm × 25 mm.
[0044] The surface pretreatment method of the additively manufactured porous channel structure is the same as that in Implementation Case 1.
[0045] The deposition scheme of the graphene layer and the copper-graphene mixture layer is the same as that of Implementation Case 2, and the number of depositions is 25 times.
[0046] The microchannel structure is filled with a copper liquid-graphene mixture, and the mixture temperature is 1096° C. An alloy material with excellent thermal conductivity is obtained.
[0047] Implementation Case 4
[0048] The mixing method of copper powder and graphene powder is the same as that of Implementation Example 2, the specifications of copper powder are the same as those of Implementation Example 3, the thickness of graphene nanosheets is about 3 layers, and the average in-plane size is about 3 μm. The mass fraction of graphene nanosheets in the mixture is 1%.
[0049] Using the same additive manufacturing method as in Example 2, a Figure 5 The cylindrical porous structure channel shown has a pore diameter of 2 mm, a minimum wall thickness between two adjacent cylinders of 0.5 mm, and a minimum wall thickness between two rows of pores of 1 mm. The pore direction is the thickness direction of the rectangular block structure, and the size of the rectangular block structure is 6 mm × 4 mm × 25 mm.
[0050] The surface pretreatment method of the additively manufactured porous channel structure is the same as that in Implementation Case 1.
[0051] The deposition scheme of the graphene layer and the copper-graphene mixture layer is the same as that of Implementation Case 2, and the number of depositions is 50 times.
[0052] The hole filling method is the same as that of implementation case 3.
Claims
1. A copper-based graphene high thermal conductivity composite alloy material and a preparation method thereof, characterized in that: Copper powder and graphene nanosheets are mixed to obtain copper-graphene mixed powder, and the copper-graphene mixed powder is manufactured into a porous channel structure using additive manufacturing technology, and then a few layers of graphene are deposited on the surface of the above-mentioned microchannel, or a few layers of graphene and pure copper or a copper-graphene mixture are alternately deposited on the surface of the porous channel, and the porous channel is filled with liquid pure copper or a liquid pure copper-graphene mixture.
2. A copper-based graphene high thermal conductivity composite alloy material and a preparation method thereof according to claim 1, characterized in that: The copper powder particles have a diameter of 1-50 μm, the graphene nanosheets have a thickness of ≤3 layers, and a diameter of less than 5 μm.
3. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 1, characterized in that: The mass fraction of graphene nanosheets in the copper-graphene mixed powder is between 0.1% and 1%.
4. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 1, characterized in that: The copper powder and graphene nanosheet powder mixing method includes ball milling mixing, ultrasonic dispersion method, deposition method and wet mixing method.
5. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 1, characterized in that: The additive manufacturing techniques include selective laser melting and selective electron beam melting.
6. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 1, characterized in that: In the additively manufactured porous channel structure, the channel size is less than 2 mm and the channel wall thickness is 0.5-2 mm.
7. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 1, characterized in that: The deposition method of few-layer graphene is chemical vapor deposition, and the deposition method of pure copper and copper-graphene mixture is electrodeposition.
8. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 6, characterized in that: The number of graphene layers deposited by chemical vapor deposition is less than 5, and the thickness of each layer of pure copper and copper-graphene mixture is less than 10μm.
9. The copper-based graphene high thermal conductivity composite alloy material and preparation method thereof according to claim 1, characterized in that: The temperature of the liquid pure copper and the liquid pure copper-graphene nanosheet mixture is less than 20°C above the melting point of pure copper.
10. A copper-based graphene high thermal conductivity composite alloy material and a preparation method thereof according to claim 9, characterized in that: The mass fraction of graphene nanosheets in the liquid pure copper-graphene nanosheet mixture is between 0.1% and 1%.
Citation Information
Patent Citations
Preparation method for graphite and copper composite heat conduction material
CN107460483A
Graphene copper composite high-thermal-conductivity film and preparation method thereof
CN117702115A
Preparation method of graphene-like-copper composite material with high thermal conductivity
CN118360514A
Cited By
Graphene / copper composite material and preparation method and application thereof
CN120719168A